Inequality and social processes in Inuit Nunangat. Issue 1 (2nd January 2016) - Lévesque, Sébastien; Duhaime, Gérard
Abstract: This article seeks to shed light on the way whereby the social inequalities typifying social formations stemming from a colonial situation become established. In particular, it takes up the case of the Canadian North and attempts to bring out the mechanisms through which the region's Inuit and non-Aboriginal populations systematically receive differentiated access to socially coveted resources. Working from a study material based on the 2006 Canadian census and 2011 National Household Survey, we developed a socio-economic profile for these populations and measured the degree of association between the variables used; education appears to play a decisive role in the access to other resources. According to our thesis, development processes framed by modernisation theory, such as those that were implemented in the second half of the twentieth century, contributed to the establishment of a system of inequality. The importing of industrial social organisation and the establishment of the market and techno-bureaucracy in Inuit Nunangat resulted in new mechanisms of resource allocation in which employment, education and income combined in ways working to the advantage of some and to the detriment of others.